Work Readiness Bagi Gen Z: Peluang Dan Tantangan - Mohammad Amin Al Kholidy (Universitas 45 Surabaya, 2023)
The trend of academic achievement scores is known as the Grade Point Average (GPA), and the technical competencies possessed by graduates are the main indicators and become the focus of users in selecting new prospective workers. This applies in almost the same way to every agency or company in Indonesia and various other places (Roth & Bobko, 2000; Sayidah et al., 2019). This conceptualization gradually begins to shift along with the dynamics of the world of work. Technical and academic abilities alone cannot guarantee and predict career success in the future of the workforce concerned (Shaturaev, 2021). Therefore, job readiness is needed for a graduate who is ready for a career. In this case, generation Z as the generation that will become the productive age group in the bonus demographic that is predicted to occur in Indonesia in 2025 requires thorough work readiness improvements. Thus, writing this article was carried out in order to find out the opportunities and challenges for Generation Z in facing the future through careful work readiness planning. Descriptive qualitative becomes a research method that the writer uses in carrying out this research. The writer obtained the data by conducting interviews with one of the grocery store owners. The results of the interviews show that the opportunity for generation Z to manage future reinforcement through work readiness is business development in the field of technology. The use of technology as a means of digital payment. It is easier to adapt in the modern world where everything is done with technology compared to the previous generation which only received technology at a less productive age. The challenges faced are the rise of cybercrime cases which are increasing along with the widespread use of technology. Not a few are part of society who are digitally illiterate so that the solution for Generation Z is to make maximum use of technology.